Anthropology of Affections in Nelson Rodrigues at the Humanities Laboratory: A Humanizing Experience in Health - Souza de Almeida, Carla Cristine (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
This work integrates the FAPESP Regular Research Project “The Pathologies of Modernity and the Medicines of Humanities: investigation and experimentation”. It intends to show how the excess of rationalism in Modernity might be understood as pathology, and thus, dehumanizing. Therefore, we seek to demonstrate in which way the humanizing experience of Literature, through an Anthropology of Affections, as seen within the work of Nelson Rodrigues, might be considered a possible “medicine” in Health.